PENGARUH PENERAPAN TERAPI THOUGHT STOPPING TERHADAP IBU POSTPARTUM DENGAN KECEMASAN DI WILAYAH KERJA PUSKESMAS RAWAT INAP SUKARAJA KOTA BANDAR LAMPUNG - Rilyani Rilyani; Dita Resi Andrianti (Malahayati Nursing Journal, 2020)
ABSTRACT:THE EFFECT OF APPLICATION OF THOUGHT STOPPING THERAPY TO POSTPARTUM MOTHERS WITH ANXIETY IN THE WORKING AREA OF PUSKESMAS RAWAT INAP SUKARAJA BANDAR LAMPUNG CITY IN THE YEAR OF 2019Backrgound: Anxiety is an emotional state that is triggered by things that are unknown and accompany new experiences such as childbirth. Postpartum mothers who experience anxiety can be caused by worry, not calm, anxiety, and nervous. Individual therapies such as thought stopping can be given to postpartum mothers who feel anxious, with the aim of reducing anxiety levels.Purpose: It was known the effect of the application of thought stopping therapy on postpartum mothers with anxiety in the working area of the Sukaraja Inpatient Health Center, Bandar Lampung City in 2019.Method: This type of research is quantitative by using quasi-experiments with one group pretest posttest. The population in this study was postpartum mothers in the working area of Sukaraja Inpatient Health Center in 2018 totaling 1,108 people. The sample in this study were 39 respondents. The instrument in this study used a questionnaire sheet. Analysis of the data in this study used the T-test.Results:The results showed the average anxiety before the application of thought stopping therapy to postpartum mothers was 18.9 with SD 2.8. Average Anxiety After applying thought stopping therapy to postpartum mothers was 12.9 with SD 2.2. The mean difference of 2 before and after thought stopping therapy was 5.89 with a p value of 0,000 (p α 0.05). The conclusions from the results of the study showed that there was an influence on the application of thought stopping therapy to postpartum mothers with anxiety in the working area of Sukaraja Hospital in Bandar Lampung in 2019. stopping to reduce or reduce anxiety.Keywords :Thought Stopping, Anxiety, Postpartum Mother INTISARI: PENGARUH PENERAPAN TERAPI THOUGHT STOPPING TERHADAP IBU POSTPARTUM DENGAN KECEMASANLatar Belakang: Kecemasan merupakan keadaan emosi yang dipicu oleh hal yang tidak diketahui dan menyertai pengalaman baru seperti melahirkan. Ibu postpartum yang mengalami kecemasan dapat disebabkan oleh rasa khawatir, tidak tenang, cemas, dan gelisah. Terapi individu seperti thought stopping dapat diberikan kepada ibu postpartum yang merasa cemas, dengan tujuan dapat menurunkan tingkat kecemasan.Tujuan: Diketahui pengaruh penerapan terapi thought stopping terhadap ibu postpartum dengan kecemasan di wilayah kerja Puskesmas Rawat Inap Sukaraja Kota Bandar Lampung Tahun 2019.Metode: Jenis penelitian ini kuantitatif dengan menggunakan quasi-eksperimen dengan one group pretest posttest. Populasi pada penelitian ini ibu nifas di wilayah kerja Puskesmas Rawat Inap Sukaraja pada tahun 2018 sejumlah 1.108 orang.Sampel pada penelitian ini sebanyak 39 responden.Instrumen dalam penelitian ini dengan menggunakan lembar kuesioner.Analisa data dalam penelitian ini menggunakan uji T-test.Hasil: Hasil penelitian menunjukkan rata-rata Kecemasan Sebelum penerapan terapi thought stopping terhadap ibu postpartum adalah 18,9 dengan SD 2,8. Rata-rata Kecemasan Sesudah penerapan terapi thought stopping terhadap ibu postpartum adalah 12,9 dengan SD 2,2. Nilai beda 2 mean sebelum dan sesudah diberikan terapi thought stopping adalah 5,89 dengan p value 0,000 ( p α 0,05). Kesimpulan dari hasil penelitian menunjukkan ada pengaruh penerapan terapi thought stopping terhadap ibu postpartum dengan kecemasan di wilayah kerja Puskesmas Rawat Inap Sukaraja Bandar Lampung Tahun 2019. Saran untuk Petugas Kesehatan agar kecemasan ibu nifas tidak tinggi maka diperlukan teknik-teknik khusus atau perlakuan khusus seperti terapi thought stopping untuk menurunkan atau mengurangi kecemasan.Kata Kunci   :Thought Stopping, Kecemasan, Ibu Postpartum